Wheat Crop Productivity in Berseem-Rice -Wheat Cropping System in Comparison with the Conventional Wheat-Rice-Wheat Cropping System Planted in Rice-Wheat Area of Punjab Pakistan: Wheat Productivity in Cropping Systems - Tanveer, SK; Hussain, Imtiaz; Hussain, Muzzammil; Sohail, Muhammad; Syed, Haider Abbas; Qamar, Maqsood; Iqbal, Mazhar Farid; Mahmood, Zahid; Waqar, Sundas (SAARC Journal of Agriculture, 2025)
Rice-wheat cropping system has an important role in ensuring the food security of Pakistan. Inclusion of a leguminous crop like Berseem (Egyptian clover) in this cropping system can have positive effects on the yields of subsequent crops. To find out the effects of different cropping systems on the productivity of wheat crop, during crop season 2014-15, wheat crop adaptation plots were planted on 10 different farmers’ fields in five major rice crop growing districts of Punjab province including Sheikhupura, Hafizabad, Mandi Bahaouddin, Gujranwala and Sialkot in two different cropping systems i.e., wheat-rice-wheat and berseem-rice-wheat. Although there were variations in grain yields of wheat crop planted under both cropping systems on different sites, but on overall basis 5.4 % more grain yield was recorded in case of berseem-rice-wheat cropping system as compared to the crop planted in conventional wheat-rice-wheat cropping system. In case of some sites less wheat crop grain yields were recorded in case of berseem-rice-wheat cropping system as compared to the crop planted in wheat-rice-wheat cropping system and it ranged from 7.5% to 16.7% but in case of maximum number of sites, more wheat crop grain yields were recorded in case of berseem-rice-wheat cropping system as compared to the crop planted in wheat-rice-wheat cropping system and these differences ranged from 5.47% to 30.76% respectively. This shows that planting of berseem crop instead of wheat after two to three years can be helpful in getting the more yields of subsequent crops, and it is also soil health and environment friendly. SAARC J. Agric., 22(2): 115-126 (2024)